Design of Solar Water Pasteurization System with Slow Sand Filtration - Khadka, Pratik Raj; Gautam, Bibek; Acharya, Nayan; Bhattarai, Basanta; Kandel, Subham; Lohani, Sunil` Prasad (Journal of the Institute of Engineering, 2020)
Solar water pasteurization system with slow sand filtration works by integration of filtration unit and pasteurization unit. The system can be utilized in rural as well as the urban areas of the country to produce reliable drinking water source. The filtration unit has layers of gravels and sand, and the pasteurization unit works by use of solar collector utilizing solar energy. The final output water is drinkable by treatment of water pathogens through the integrated units. The use of two systems: Pasteurization unit and Filtration unit independently checks and corrects the flaw of the other to produce clean and pure drinking water. The output water from the integrated system is tested and found to have reduced TDS from 159 mg/l to 137 mg/l, E. coli count from 6 CFU/100ml to 0 CFU/100ml and Total coliform count from 52 CFU/100ml to 0 CFU/100ml. This hybrid system uses solar energy for water pasteurization so it can be utilized effectively for drinking water purposes.